2022
DOI: 10.47119/ijrp10011011020223952
|View full text |Cite
|
Sign up to set email alerts
|

Discourse Analysis on the Critiques of Grade-10 World Literature Students: Approaches to Literary Criticism in Focus

Abstract: This qualitative corpora-based study examined the content of the critiques of Grade 10 world literature students in one of the Division of Davao del Norte schools as they analyzed a story reflected in the Self-Learning Module. This study aimed to identify the approaches to literary criticism used by the students as their literary frameworks in interpreting the story. These approaches were based on the Literary Theory and Schools of Criticism proposed by Dobie (2011). It also investigated how the approaches to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Despite government efforts to improve literacy rates in the Philippines, recent studies have shown that many students need help with reading comprehension, vocabulary development, and critical thinking skills. Aside from dwelling only on the surface meaning of texts, they could not also evaluate the factual information and infer meaning from certain texts (Idulog et al, 2023;Gulo & Deloy, 2022). The evidence of this phenomenon was further reinforced in the previous results of PISA Report in 2019 which illustrated that Philippines ranked lower than majority of its Southeast Asian counterparts, let alone in the global setting.…”
Section: Introductionmentioning
confidence: 97%
“…Despite government efforts to improve literacy rates in the Philippines, recent studies have shown that many students need help with reading comprehension, vocabulary development, and critical thinking skills. Aside from dwelling only on the surface meaning of texts, they could not also evaluate the factual information and infer meaning from certain texts (Idulog et al, 2023;Gulo & Deloy, 2022). The evidence of this phenomenon was further reinforced in the previous results of PISA Report in 2019 which illustrated that Philippines ranked lower than majority of its Southeast Asian counterparts, let alone in the global setting.…”
Section: Introductionmentioning
confidence: 97%